2004
DOI: 10.4049/jimmunol.172.11.6568
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to DNA in (NZB × NZW)F1 Mice That Inherit an Anti-DNA VH as a Conventional μ H Chain Transgene but Not as a VH Knock-in Transgene

Abstract: Lupus-prone (NZB × NZW)F1 (BWF1) mice were made transgenic (Tg) for an anti-DNA Ab inherited either as a conventional VH3H9-μ H chain Tg (3H9-μ) with or without a conventional Vκ8-κ Tg, or a VH3H9 VH knock-in Tg allele (3H9R) with or without a Vκ4 Vκ knock-in Tg allele (Vκ4R). VH3H9 yields an anti-DNA Ab with most L chains including an anti-ssDNA with the Vκ8 Tg and an anti-dsDNA with the Vκ4 Tg. BWF1 mice that inherited the conventional 3H9-μ had normal serum IgM, little to none of which was encoded by 3H9-μ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
2
13
1
Order By: Relevance
“…Sle3, the third NZW lupus susceptibility locus also promoted anti-DNA Ab production in response to prolactin in another anti-DNA BCR Tg model [121]. In contrast to these findings, and previous reports on this model [59,119], analyses of lupus-prone BWF1 mice bearing the anti-DNA ''3H9'' Tg revealed that B-cells from such mice displayed normal tolerance to DNA in that they were adequately anergized; the reasons for these differences are presently unknown [122].…”
Section: Molecules Involved In Lymphocyte Apoptosis/survivalcontrasting
confidence: 77%
“…Sle3, the third NZW lupus susceptibility locus also promoted anti-DNA Ab production in response to prolactin in another anti-DNA BCR Tg model [121]. In contrast to these findings, and previous reports on this model [59,119], analyses of lupus-prone BWF1 mice bearing the anti-DNA ''3H9'' Tg revealed that B-cells from such mice displayed normal tolerance to DNA in that they were adequately anergized; the reasons for these differences are presently unknown [122].…”
Section: Molecules Involved In Lymphocyte Apoptosis/survivalcontrasting
confidence: 77%
“…To analyze the mechanisms for dysregulation of the autoantibody response in TLR7 over-expressing W/B males and for the loss of B cell tolerance following exogenous IFNα administration in females we generated W/B mice bearing the site directed anti-CL/DNA autoantibody V H transgene 3H9 (9). V H 3H9 is a heavy chain isolated from an anti-DNA antibody spontaneously produced in MRL/lpr mice; it pairs with a wide variety of V light chains to generate DNA and non-DNA binding antibodies as well as low affinity anti-CL antibodies (10).…”
Section: Introductionmentioning
confidence: 99%
“…The present results may explain why autoimmune female BWF1 transgenic for V H of the 3H9 anti-DNA mAb (33, 34) do not develop nephritis (35). 3H9 mAb binds DNA and chromatin (36) but does not bind BM.…”
Section: Discussionmentioning
confidence: 69%
“…BALB/c mice injected with the 3H9 hybridoma had relatively low glomerular immunofluorescence and disease scores compared with mice injected with 163p.77 or 163p.132 hybridomas (31). The majority of anti-DNA hybridomas from V H 3H9 transgenic BWF1 had V H 3H9 H chains (39). Likely those mAbs could not bind BM and could not initiate disease.…”
Section: Discussionmentioning
confidence: 99%